The genome sequence of the Common Goldeneye, Bucephala clangula (Linnaeus, 1758) [version 1; peer review: 2 approved] - Rosa Lopez Colom; Michelle F. O’Brien (Wellcome Open Research, 2025)
We present a genome assembly from a male Bucephala clangula (Common Goldeneye; Chordata; Aves; Anseriformes; Anatidae). The genome sequence has a total length of 1,190.92 megabases. Most of the assembly (95.05%) is scaffolded into 40 chromosomal pseudomolecules, including the Z sex chromosome. The mitochondrial genome has also been assembled, with a length of 16.63 kilobases.